Importance of international unification of diagnostic procedures for basic and specific preparation of advanced wrestlers - Baic, M.; Pekas, D. (International Journal of Wrestling Science, 2022)
Raising the level of fitness preparation is important segment of training programs and a condition foradequate preparation of wrestlers for top achievements in sports. Inadequate "foundation" of fitness preparation in younger age groups causes narrowing of sports achievements later in the sports career. Furthermore, the importance of certain fitness abilities for success in a fight is different for wrestlers of different styles (Greco-Roman or freestyle), of different ages and differentweight groups. These facts have been known for many years (Starosta and Trecewski 1998; Baic et al., 2009; Baic, 2006), and many authors in Croatia monitored the state of fitness preparedness of wrestlers of different age groups (Maric i sur, 2003; Baic, 2003, 2006; Cvetkovic et al., 2005; Sertic et al., 2005 and many others). Earlier investigations did not consider the importance of coordination abilities for success in wrestling Tumanjan GS, (1984), Cabric M, (1976). A large number of researchers were mainly engaged in researching the strength of wrestlers (Clarke, et al, 1984, Song and Garvie (1980) Rasch et al, 1961; Kelly et al, 1978) or specific endurance (Horswill, et al (1989). Preobrazenski (1978) divides wrestlers into two categories 1. those who conquer by strength 2. those who win with endurance (high pace of battle)